Organization and Regulation of Soybean SUMOylation System under Abiotic Stress Conditions - Li, Yanjun; Wang, Guixin; Xu, Zeqian; Li, Jing; Sun, Mengwei; Guo, Jingsong; Ji, Wei (Frontiers in Plant Science, 2017)
Covalent attachment of the small ubiquitin-related modifier, SUMO, to substrate proteins plays a significant role in plants under stress conditions, which can alter target proteins’ function, location, and protein-protein interactions. Despite this importance, information about SUMOylation in the major legume crop, soybean, remains obscure. In this study, we performed a bioinformatics analysis of the entire soybean genome and identified 40 genes belonged to six families involved in a cascade of enzymatic reactions in soybean SUMOylation system. The cis-acting elements analysis revealed that promoters of SUMO pathway genes contained different combinations of stress and development-related cis-regulatory elements. RNA-seq data analysis showed that SUMO pathway components exhibited versatile tissue-specific expression patterns, indicating coordinated functioning during plant growth and development. qRT-PCR analysis of 13 SUMO pathway members indicated that these genes were differentially responded to NaCl, heat and ABA treatments at 1, 6, 12, and 24 h, respectively. Furthermore, western blot analysis was performed to detect the SUMOylation dynamics in soybean roots under abiotic stress. Collectively, this study defined the organization of the soybean SUMOylation system and implied an essential function for SUMOylation in soybean abiotic stress responses.